Enkripsi Gambar Berdasarkan Modifikasi Bit Piksel Dengan Menggunakan Perpaduan Logistic Map Dan Henon Map - Ardita, I Kadek Aldy Oka; Muliantara, Agus; Anom Cahyadi Putra, I Gusti Ngurah; Sanjaya ER, Ngurah Agus; Made Mahendra, Ida Bagus (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2022)
Data theft using malware attacks in this digital era can attack smartphones and cloud servers, in 2018 there was the theft of photos belonging to Aryono Huboyo Djati. Theft can be prevented by applying cryptographic techniques. The purpose of this study was to determine the ability to combine Logistic Map and Henon Map in image encryption and decryption. These two theories were chosen because they are sensitive, with a small change in the input value will have a very significant impact on the output value. First step is changing the image into a matrix and randomizing using the Logistic Map algorithm and then continuing with the XOR process for each pixel bit using the Henon Map algorithm. in this study the encrypted image obtained an average MSE value exceeding 400 and the average PSNR value less than 10dB, this indicates that the cipher image is different from the plain image, and the decryption results show the average MSE value is 0 and the average PSNR value average is 100, this indicates that there is no difference between the description image and the original image